Low back pain in 17 year olds has substantial impact and represents an important public health disorder: a cross-sectional study - O'Sullivan, Peter; Beales, Darren; Smith, Anne; Straker, Leon (BioMed Central Ltd, 2012)
Background: Prevalence of low back pain (LBP) rises rapidly during adolescence, reaching adult levels by the age of 18. It has been suggested that adolescent LBP is benign with minimal impact, despite limited evidence. Methods: The aim of this study was to investigate the impact of LBP and the influence of chronicity, gender and presence of other spinal pain comorbidities at age 17. Subjects (n = 1283) were categorised according to experiencing current and chronic LBP, gender and presence of other areas of spinal pain. LBP impact was ascertained via questions regarding seeking professional assistance, using medication, missing school/work, limited normal or recreational physical activity and health related quality of life (HRQOL). Results: 12.3% of participants reported current but not chronic LBP, while 19.9% reported current chronic LBP. LBP was more commonly reported by females than males. Other spinal pain comorbidities were common in the LBP groups. Impact was greater in subjects with chronic LBP, in females and in those with other spinal pain comorbidities. Conclusion: LBP, and particularly chronic LBP, has a significant negative impact at 17 years. It is commonly associated with care seeking, medication use, school absenteeism, and reduced HRQOL. These findings support that adolescent LBP is an important public health issue that requires attention.